Hamlets, environment and landscape: a project to give value Apennines - Ronzoni, Maria Rosa (TeMA - Journal of Land Use, Mobility and Environment, 2022)
I will describe a multi-scalar project concerning the municipality of Castelnovo ne’ Monti, where I try to develop spaces for socializing in compliance with the distancing constraints that are required at us. The project strengthens structuring elements of this territory by resorting to various interventions. The organization of the small villages connected together working as an integrated system, the insertion of a new central place, the eco-camping project and the three pine forests regeneration without forgetting the desire to spread the interest in two authentic treasures: Pietra of Bismantova and Gessi Triassici of the Secchia valley.